2010
DOI: 10.1037/a0019749
|View full text |Cite
|
Sign up to set email alerts
|

A review of EEG, ERP, and neuroimaging studies of creativity and insight.

Abstract: Creativity is a cornerstone of what makes us human, yet the neural mechanisms underlying creative thinking are poorly understood. A recent surge of interest into the neural underpinnings of creative behavior has produced a banquet of data that is tantalizing but, considered as a whole, deeply self-contradictory. We review the emerging literature and take stock of several long-standing theories and widely held beliefs about creativity. A total of 72 experiments, reported in 63 articles, make up the core of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
573
2
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 765 publications
(604 citation statements)
references
References 90 publications
(340 reference statements)
16
573
2
13
Order By: Relevance
“…Each of these cognitive functions must be engaged during this initial phase of the creative process. Indeed, a role for the MPFC during spontaneous creative activity has been confirmed by many neuroimaging studies using different paradigms and imaging modalities [Dietrich and Kanso, 2010]. …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Each of these cognitive functions must be engaged during this initial phase of the creative process. Indeed, a role for the MPFC during spontaneous creative activity has been confirmed by many neuroimaging studies using different paradigms and imaging modalities [Dietrich and Kanso, 2010]. …”
Section: Discussionmentioning
confidence: 97%
“…Although many regions have been implicated, the most frequent observations have emphasized the frontal lobe [Dietrich and Kanso, 2010]. Activation of the medial prefrontal cortex (MPFC) is perhaps the most consistent finding across studies [Dietrich and Kanso, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism might also explain the finding of a positive association between alpha brain waves and verbal creativity (Fink, Grabner, Benedek, & Neubauer, 2006;Jausovec, 2000;Martindale & Hasenfus, 1978;Martindale & Hines, 1975). However, not all EEG studies find such an association (Danko, Shemyakina, Nagornova, & Starchenko, 2009;Molle, Marshall, Wolf, Fehm, & Born, 1999;Shemyakina & Danko, 2007) and the conditions under which it appears remain to be elucidated (Dietrich & Kanso, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies on the laterality or hemispheric effect of creative thinking have demonstrated that the left hemisphere is generally associated with analytical thinking, and the right hemisphere is associated with creative thinking. Some studies on insight problem solving support a right hemispheric dominance of insight [52], but most studies exhibit the left hemispheric effect of insight [82]. Both hemispheres are involved in creative insight, and the interaction between the two hemispheres is critical.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%